Sexual Self-Concept Discrepancies Mediate the Relation between Gender Dysphoria Sexual Esteem and Sexual Attitudes in Binary Transgender Individuals. Issue 4 (4th May 2022) - Kennis, Mathilde; Duecker, Felix; T'Sjoen, Guy; Sack, Alexander T.; Dewitte, Marieke
ABSTRACT: Sexual responding in transgender people has typically been investigated from a medical and functional perspective. Aligning with the biopsychosocial model, it is however equally important to consider psychological aspects of sexuality in this population. We propose that the Sexual Self-Concept (SSC) theory offers a valuable framework to understand (sexual) wellbeing in transgender people, while Self-Concept Discrepancy (SCD) theory could offer an explanation of the mechanisms underlying negative SSCs related to gender dysphoria. We investigated differences in SSC (consisting of sexual esteem, sexual attitudes, and sexual self-efficacy) in 197 binary transgender and 205 cisgender individuals using an online survey and explored the mediating role of actual/ideal self-discrepancies in explaining the relation between gender dysphoria and SSC. Transgender and cisgender individuals differed significantly in seven out of eight components related to sexual esteem and sexual attitudes. Actual/ideal self-discrepancies mediated the relationship between gender dysphoria and the SSC in transgender individuals for the sexual esteem components related to body perception, conduct, and attractiveness, as well as for sexual anxiety. We found no relation between gender dysphoria and the other SSC components in this group. We conclude that SSC discrepancies could be a valuable treatment target to improve transgender individuals' sexual esteem and sexual attitudes.